A comprehensive review of recent development in extraction and encapsulation techniques of betalains - ZANNOU, Oscar; CHABI, Ifagbémi Bienvenue; KAYODE, A. P. Polycarpe; GALANAKIS, Charis (My University, 2023)
Betalains are attractive natural pigments with potent antioxidant activity, mainly extracted from the roots, tubers, leaves, flowers, and fruits of certain plants and some fungi. they constitute a reliable alternative to synthetic dyes used in the food industry and are considered toxic for consumers. in addition, there is convincing evidence of their health benefits for consumers. However, betalains are highly unstable to environment factors, such as light, heat, oxygen, water activity, and pH change which can be degraded during food processing, handling, storage, or delivery. therefore, newly developed extraction methods and micro/nano-encapsulation techniques are currently applied to enhance the extraction yield, solve their instability problems, and improve their application in the food industry. this article aims to summarize the new advanced extraction methods of betalains, discussing the recent encapsulation techniques concerning the different encapsulating materials utilization. Betalains, natural pigments with potent antioxidant activity, are increasingly extracted from the roots, tubers, leaves, flowers, and fruits of certain plants and some fungi as safe alternatives to synthetic food dyes used in the food industry. However, their susceptibility to degradation during food processing, storage, and delivery poses challenges. Recent developments in extraction methods (e.g., supercritical fluid, pressurized liquid, ultrasound- and microwave-assisted, and enzyme-assisted) enhance betalain recovery, minimizing degradation. encapsulation techniques using biopolymers, proteins, lipids, and nanoparticles protect betalains from environmental factors, extending shelf life and enabling controlled release. these advancements offer improved extraction efficiency, reduced solvent use, shorter processing times, and enhanced stability. integration of these techniques in the food industry presents opportunities for incorporating betalains into various products, including functional foods, beverages, and dietary supplements. By addressing stability challenges, these developments support the production of innovative, healthier food items enriched with betalains. this article provides an overview of recent advancements in betalain extraction and encapsulation, highlighting their potential applications in the food industry.
Keywords: Betalains; extraction; novel methods; health beneft; encapsulation; nanoparticle